Effects of supranationalism on environmental policy resilience : an analysis of the EU emissions trading system - Baran, Hunca Seyfettin. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2023., 2023)
This research examines the effects of supranationalism on the viability and resilience of environmental policies through an analysis of the EU Emissions Trading System (ETS). It hypothesizes that the increased level of supranationalism has a positive effect on the viability and resilience of environmental policies. This thesis examines the internal debates in the EU, ETS- related reports, and policy design choices to uncover patterns that can increase viability and resilience. The main argument is that the increased level of supranationalism caused the ETS to be more centralized and made non-compliance harder for the EU Member States as well as several Member State-internal stakeholders. This thesis also argues that the information channels between the Commission and the stakeholders increased the resilience of ETS by allowing the Commission the tailor it according to business stakeholder needs. This research focuses on the puzzle of how the EU, a multinational structure with many actors, was able to build and sustain its ETS.
Keywords: Supranationalism -- European Union countries.; Environmental policy -- European Union countries.; Emissions trading -- European Union countries.; Resilience (Ecology)